Disagreement between Parents and Adolescents for Use of Social Media- A Critical Analysis - Patra, Kshiptimayee; Gogoi, Sampreety; Saikia, Jinamoni (International Journal of Bio-resource and Stress Management, 2021)
Adolescents spend most of their time on social media for which they started ignoring other important activities and interacts less in their real surroundings. They think that social media has given them the opportunity and the platform for improving their social skills, and sharing their creativity. Whereas parents feel that their children are wasting their precious time on social media. As the perceptions of parents and adolescents are different from each other regarding the use of social media, there starts a disagreement between parents and adolescents regarding the use of social media. The present study was an attempt to find out the reasons for disagreement between parents and adolescents for use of social media. By using a multi-stage sampling procedure, a sample of 118 numbers of adolescents and their respective parents, (236 samples) were selected from five schools of the Jorhat block of Assam. A self-constructed questionnaire was prepared to collect the required information from the respondents. The results revealed that there was disagreement in the areas of academic performance and socialization between parents and adolescents for use of social media, while no disagreement was present in the area of health.